Incriminatory utopias: Utopian visions creating scapegoats. (December 2022) - Drousioti, Kalli; Papastephanou, Marianna
Many utopian visions operate by scapegoating an Otherness. They blame an 'enemy' for an unbearable, dystopian current reality, holding the 'enemy' responsible for it or for obstructing the passage to a desired, new reality. Then they exclude (or even promise the elimination of) this 'enemy'. Despite the renewed interest in utopias, such utopian frames remain theoretically neglected or, worse, they are considered typical of the logical structure of utopianism. This paper aims to show that this issue merits a different political-philosophical attention. We begin with operations of utopian predicates in the relevant scholarship and distinguish them from the operations of the term 'incriminatory' that we are introducing. We term incriminatory the kind of utopian frame whose future-oriented, idealized and desired image is constructed in and through an incriminated 'Other'. We indicate the re-conceptualizing merits of this new term and then we discuss the affirmative utopianism that does not incriminate a specific Other. Our main argument, which we deploy contra Yannis Stavrakakis's position, is that utopias are not unavoidably or inherently incriminatory.